Carboniferous auloporids from the Iberian Peninsula: palaeocology, diversity, and spatio-temporal distribution - Coronado, I.; Rodríguez, S. (Journal of Iberian Geology, 2014)
Auloporid corals are common in the Palaeozoic and very frequent in the Carboniferous buildups of the Iberian Peninsula. The aim of this study is to analyze the diversity of these corals through a taxonomical recognition of the species and morphotypes that occur in the Iberian Peninsula. Eighteen sections have been sampled between the Ossa-Morena (Mississippian) and Cantabrian (Pennsylvanian) zones dated as upper Viséan to early Kasimovian. In addition, other localities where auloporids occur and are cited in the literature have been also used for this study. The taxonomical identification has been carried out using the criteria proposed by Tchudinova (1980) with little modifications. Thus, eighteen morphotypes and two species belonging to nine nominal genera have been identified (Multithecopora sp. A-H, Syringopora sp. A-B, Aulopora sp. A-B, Cladochonus sp. A-B, Syringoalcyon sp., Roemeripora sp., Sinopora sp., Mastopora? sp., Multithecopora hontoriense and Neomultithecopora cantabrica). Through a classical microfacies study, the environments where the auloporids lived have been identified, as well as the growth patterns and the features of sedimentation. Finally, a preliminary biostratigraphic range chart for the Carboniferous auloporoids from the Iberian Peninsula has been achieved.